Analysis of Mangrove Ecosystems and Number of Plants on Air Pollution Reduction by Mangrove Plants - Rusmayadi, Gusti; Zulfikhar , Rosa; Angrianto, Rusdi; Sutiharni, Sutiharni; Tuhumena, Veronica. L. (West Science Agro, 2024)
This research investigates the intricate relationships between Mangrove Ecosystems, the Number of Plants within these ecosystems, and their collective impact on Air Pollution Reduction. Employing a structural equation model, the study explores the quantitative dynamics across diverse mangrove ecosystems globally. The findings reveal a significant positive relationship between Mangrove Ecosystems and Air Pollution Reduction, emphasizing the pivotal role of mangroves as biofilters. Additionally, the study highlights the importance of vegetation density, with a higher Number of Plants correlating with a meaningful reduction in air pollution. The global implications underscore the applicability of mangrove-mediated air pollution reduction across diverse geographical contexts. The results provide valuable insights for policymakers, environmental managers, and conservationists, advocating for the conservation and restoration of mangrove habitats as an effective and sustainable strategy for mitigating the adverse effects of air pollution.